The Book of Nahum and the Book of Jonah: Debate Within the Twelve Prophets? - Strzałkowska, Barbara (Collectanea Theologica, 2021)
Since antiquity, the issue of the inconsistency between the Book of Nahum and the Book of Jonah has been addressed, one regarding both its content and its message. At various times, it was settled in different ways. The current state of biblical research seems to allow us to put forth a daring thesis that both Books have more in common than merely Nineveh as the subject matter, which they approach from a different angle. There seem to be grounds to see these two Books as vestiges of an intracanonical debate waged within the Book of the Twelve.